2022
DOI: 10.3390/jcm11216587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microencapsulated Sodium Butyrate, Probiotics and Short Chain Fructooligosaccharides in Patients with Irritable Bowel Syndrome: A Study Protocol of a Randomized Double-Blind Placebo-Controlled Trial

Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal disease in the pathogenesis of which gut dysbiosis may play an important role. Thus, probiotics, prebiotics, or microbiota metabolites, such as butyric acid, are considered to be effective therapy for IBS. However, there are still no trials presenting the efficacy of these three biotic components administered simultaneously. This study aims to evaluate the effects of the product comprising sodium butyrate, probiotics, and short-chain fructooligosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Results showed the preparation of 1.1 µm microparticles with excellent ROS scavenging ability in cell experiments and a 40% reduction in disease activity index scores in animal experiments (Figure 4D) [131]. In fact, multicomponent microencapsulation could generate better results, as reported by G ąsiorowska et al The authors showed a clinical study using sodium butyrate microparticles, probiotics, and short-chain fructooligosaccharides in patients with Irritable Bowel Syndrome (IBS), a functional gastrointestinal disorder that can cause symptoms similar to IBD but without damaging the gastrointestinal tract [132]. Probiotics used were two Lactobacillus strains (L. rhamnosus and L. acidophilus) and three Bifidobacterium strains (B. longum, B. bifidum, and B. lactis), and results showed that this combination could be beneficial for an alternative treatment of IBD, as it restores the disturbed functionality of the intestinal microbiota [115].…”
Section: Microparticle-based Drug Delivery Systemsmentioning
confidence: 62%
“…Results showed the preparation of 1.1 µm microparticles with excellent ROS scavenging ability in cell experiments and a 40% reduction in disease activity index scores in animal experiments (Figure 4D) [131]. In fact, multicomponent microencapsulation could generate better results, as reported by G ąsiorowska et al The authors showed a clinical study using sodium butyrate microparticles, probiotics, and short-chain fructooligosaccharides in patients with Irritable Bowel Syndrome (IBS), a functional gastrointestinal disorder that can cause symptoms similar to IBD but without damaging the gastrointestinal tract [132]. Probiotics used were two Lactobacillus strains (L. rhamnosus and L. acidophilus) and three Bifidobacterium strains (B. longum, B. bifidum, and B. lactis), and results showed that this combination could be beneficial for an alternative treatment of IBD, as it restores the disturbed functionality of the intestinal microbiota [115].…”
Section: Microparticle-based Drug Delivery Systemsmentioning
confidence: 62%
“…Using a feedback artificial neural network designed for a certain problem and giving full play to the high-speed computing ability of the computer, the optimal solution may be found quickly. This technology can be applied in clinical medicine to detect the pathogenesis of gastroenterologyneuroscience [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%